O planejamento urbano participativo: avaliação da experiência participativa na revisão do plano diretor de Fortaleza - Lima, Aline Gomes (2024)
With one of the highest urbanization rates in the world, Brazil is home to an urban population of 124.1 million people, according to data from IBGE in 2022. This study aims to evaluate social participation in urban planning in municipalities, with a specific focus on participation during the Revisão do Plano Diretor de Fortaleza. To achieve this, a theoretical analysis is conducted in the areas of public policies, urban planning, territory, participation, and policy evaluation; investigation of the legal frameworks that underpin Plano Diretor at the national level; and description and discussion of the development of the process of promoting and incentivizing participation. The methodology proposed by Ozanira Silva e Silva (2013) is adopted, combined with Bardin's content analysis. The work included interviews conducted with a sample of ten interlocutors in Stages 1 and 2 of the revision, exploring the following starting question: "How has the Municipal Government of Fortaleza promoted and encouraged social participation during the process of revising Plano Diretor Municipal de Fortaleza?" It is worth noting that the Plano Diretor is mandatory for municipalities with more than twenty thousand inhabitants, as well as for cities belonging to metropolitan regions and urban agglomerations, and places where the municipal public authority plans to use the instruments provided for in paragraph 4 of article 182 of the Constituição Federal (1988), among other criteria. Despite efforts to foster spaces for dialogue and social participation through participatory methodologies, it is observed that access to these spaces is still restricted, resulting in a virtually nonexistent representation of the population. This reality indicates a predominantly participatory role for actors already directly involved in urban public policies, such as social movements, as well as those related to the economic development of the municipality, giving them a specialized character. The promotion and encouragement of participation, whether in person or virtually, remain a challenge, requiring effective mobilization and awareness-raising strategies, especially to involve the population in decisions of such a nature.